Conformance testing of Extensible Authentication Protocol implementations - Nikeshin, A.V.; Shnitman, V.Z. (Trudy Instituta sistemnogo programmirovaniâ, 2019)
The paper presents a model-based approach to conformance testing of Extensible Authentication Protocol (EAP) implementations. Conformance testing is the basic tool to ensure interoperability between implementations of a protocol. Using UniTESK technology allows automating the verification of network protocols based on their formal models. Additional applying of mutation testing allows evaluating the robustness of the implementations to receive incorrect packets. We applied the test suite to several implementations of EAP and present brief results. This approach has proved to be effective in finding several critical vulnerabilities and other specification deviations in the EAP implementations.